Radikalisme Agama: Mati Martir atau Bunuh Diri? Pemahaman Teologis Konsep Keselamatan dalam Kaitannya dengan Kelompok Radikal Kristen - Efrim Wildatri (Sabda: Jurnal Teologi Kristen, 2022)
This paper aims to straighten out an understanding of martyrdom in relation to acts of radicalism in Christianity. radicalism which is synonymous with violence has always succeeded in providing a record of how many lives were victims of this action. Many think that the perpetrators of radicalism who died in their actions were martyrs. However, the concept of martyrdom must be seen further, because martyrdom is not just a concept of sacrificing one's life, but also a life that manifests faith through the actions of daily life. These two concepts also involve the theory of suicide to see clearly whether radical actions are more worthy of being called martyrdom or suicide. Furthermore, the author wants to provide an explanation regarding the Christian view, especially regarding the concept of salvation in viewing radicalism actions that occur, whether they are in accordance with God's will or contrary, and what actions should be carried out as people who believe and who have been chosen to be saved. In this paper, the author uses qualitative research methods by conducting literature studies to obtain a conclusion from the problem being studied.